Additional tests of multi-index asset pricing models: evidence from an emerging market. Issue 4 (2nd October 2017) - Danışoğlu, Seza
ABSTRACT: This study provides comprehensive evidence on the performance of asset pricing models in an emerging market setting. Tests are conducted on portfolios formed based on Fama–MacBeth betas, Fama–French size and book-to-market (B/M) factors, Carhart's short- and long-term past returns and Pastor and Stambaugh's liquidity beta. This is one of the first studies to provide emerging market evidence on Pastor and Stambaugh's liquidity beta measuring a firm's sensitivity to changing levels of market-wide liquidity. Results of the study are supported by metrics such as confidence intervals around the R 2 values and the Gibbons-Ross-Shanken test. Similar to previous findings, the market factor is positive and significant even when models are augmented by the size and B/M factors that are themselves consistently significant and positive. Contrary to evidence from developed markets, contrarian, not momentum, strategies are preferred among the investors, especially for larger firms. Larger firms also are perceived to be less vulnerable when market-wide liquidity decreases.